Antagonistic effect of andrographolide on cigarette smoke-induced lung injury in mice - Jia-li LIU; Gan-ling DING; Jia-qi WANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore protective effect of andrographolide on lung injury in mice exposed to cigarette smoke, and to provide evidences for the prevention and treatment of chronic obstructive pulmonary disease (COPD). MethodsForty mice were randomly divided into a control group (A), cigarette smoke exposure group (B), normal saline group (C), and andrographolide group (D). All the mice were exposed to cigarette smoke (300 mg/m3) for one hour, twice a day, five days in a week for 12 weeks, except for those of group A. The mice of group D were treated with an intraperitoneal injection of andrographolide at dose of 20 mg/kg body weight once a week after last cigarette smoke exposure during the week and the mice of group C were treated simultaneously but with 200 μL saline. By the completion of all the treatments, lung tissue and blood samples of the mice were collected for determinations of alveolus mean lining interval (MLI), mean alveolar area (MAA), interleukin-6 (IL-6)/interleukin-8 (IL-8)/matrix metalloproteinase-9 (MMP-9) in serum and bronchoalveolar lavage fluid (BALF). Correlations among IL-8, IL-9 and MMP-9 were analyzed. ResultsThe MLI, MAA, IL-6, IL-8 and MMP-9 of the mice exposed to cigarette smoke were significantly higher than those of the control mice. Compared with those of the mice with cigarette smoke exposure, the MLI, MAA, IL-6, IL-8 and MMP-9 were significantly decreased in the mice of andrographolide group. In BALF, the concentration of IL-6 and IL-8 were significantly correlated with that of MMP-9. ConclusionAndrographolide could reduce BALF MMP-9, exerting an anti-inflammatory effect on lung injury induced by cigarette smoke exposure in mice.